A meta‐analysis of inositol for depression and anxiety disorders. (3rd December 2013) - Mukai, Tomohiko; Kishi, Taro; Matsuda, Yuki; Iwata, Nakao
<x xml:space="preserve">Abstract</x> Objective This study is a meta‐analysis of inositol as a treatment for depression and anxiety disorders. Methods PubMed, Cochrane Library database, and PsycINFO were searched up to 14 August 2013. A systematic review and meta‐analysis of double‐blind, randomized, placebo‐controlled trials (RCTs) were conducted comparing inositol for depressed or anxiety disorder patients. Results Seven RCTs in depression (two bipolar depression studies, one bipolar depression and major depressive disorder (MDD) study, two MDD studies, and two premenstrual dysphoric disorder (PMDD) studies) (n = 242) were identified. Four RCTs in anxiety disorders (two obsessive–compulsive disorder studies, one panic disorder study, and one posttraumatic stress disorder study) (n = 70) were also identified. There were no statistically significant effects of inositol on depressive, anxiety, and obsessive–compulsive symptoms and discontinuation (all‐cause, side effects, and worsening psychiatric symptoms). However, inositol had marginally more responders in depression than placebo (p = 0.06), and inositol showed a trend towards superior efficacy for depressive symptoms in patients with PMDD (p = 0.07). Inositol marginally caused gastrointestinal upset compared with placebo (p = 0.06). Conclusions Our results suggest that inositol may be beneficial for depressed patients, especially those with PMDD. The main limitation of this report is that a small number of studies were included in this meta‐analysis. Copyright © 2013 John Wiley & Sons, Ltd.